2018
DOI: 10.1002/ldr.3103
|View full text |Cite
|
Sign up to set email alerts
|

A spatial simulation model for karst rocky desertification combining top‐down and bottom‐up approaches

Abstract: Karst rocky desertification (KRD) is a serious ecological and environmental issue threatening southwestern China. The evolution of KRD calls for predicting its potential expansion or contraction, to support policy‐making for combating KRD. A spatial model named ‘SDKRD’ for simulating KRD dynamics was developed in this study. The novelty of it is the ability to explore spatially local KRD evolution and integrate this information into a global estimation. The SDKRD model consists of three modules: a global KRD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The statistical significance of C ks and I K$S in this proposed model could also be further tested. Given the complex coupling relationship between KRD and social-economic development measured in this study, it is suggested that these be incorporated into model simulations for KRD succession and socialeconomic development (Abdollahian et al, 2015;Helldén, 2008;Xu & Zhang, 2018). In particular, the inverted U-shaped curve for C ks as a function of different urbanization levels should be considered for improving the model's accuracy.…”
Section: Coupling Characteristics Between Karst Rocky Desertification and Social-economic Activitymentioning
confidence: 99%
“…The statistical significance of C ks and I K$S in this proposed model could also be further tested. Given the complex coupling relationship between KRD and social-economic development measured in this study, it is suggested that these be incorporated into model simulations for KRD succession and socialeconomic development (Abdollahian et al, 2015;Helldén, 2008;Xu & Zhang, 2018). In particular, the inverted U-shaped curve for C ks as a function of different urbanization levels should be considered for improving the model's accuracy.…”
Section: Coupling Characteristics Between Karst Rocky Desertification and Social-economic Activitymentioning
confidence: 99%
“…As one of the most fragile terrestrial ecosystems [5, 6], Karst landforms are especially developed and widespread in soluble rock areas, such as the Nullarbor Plain in Australia, the Western Highland Rim in the United States, and the Yunnan-Guizhou Plateau in China. In Southwest China, Karst rocky desertification has become a serious threat to local agriculture, forestry, and livestock husbandry [7, 8], and Karst soils have poor water-holding capacity and nutrient cycling ability. The new P. edulis variety ‘Pingtang 1’ is widely cultivated in the Karst areas of Guizhou.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the degeneration of water conservation services further aggravated environmental degradation [6]. In particular, the vulnerable karst ecosystem, with its special geological conditions [7], has been affected by external environmental impact and has suffered serious vegetation degradation, and gave rise to rocky desertification [8][9][10]. Among them, water and soil loss are the core problem of rocky desertification formation [11].…”
Section: Introductionmentioning
confidence: 99%